MAIN HEALTH INDICATORS OF INFANTS FROM INDUCED SINGLE PREGNANCY - Соболева, Мария Константиновна; Киншт, Дарья Александровна (Mother and Baby in Kuzbass, 2020)
The aim of the research - to study the influence of the reproductive health of parents with a history of infertility, the somatic health of the mother and the course of pregnancy on the health of children born with singleton IVF pregnancy. Material and methods. А retrospective case-control study was carried out. The main group consisted of all newborns from singleton ART born in the Avicenna medical center (Novosibirsk) in the period from 2007 to 2017. (n = 409). The control group consisted of 210 newborns from singleton spontaneous pregnancy, without a history of infertility of parents, whose mothers’ obstetric and gynecological history was not burdened (the parity of pregnancies is equal to the parity of childbirth), born in the same period. Results. Children born of ART, despite the multiple factors associated with the somatic health of the mother and the complicated course of pregnancy, have similar characteristics in the main groups of pathological conditions / nosologies with children born in couples without a history of infertility. Conclusion. Comprehensive, interdisciplinary medical support for couples at all stages of infertility treatment, with the timely detection and correction of emerging complications of pregnancy, allows to neutralize the negative factors associated with the reproductive and somatic health of parents, and lead to the birth of children with ART, comparable in the main indicators of health to children, born from a spontaneous pregnancy.